1976
DOI: 10.1111/j.1095-8649.1976.tb04669.x
|View full text |Cite
|
Sign up to set email alerts
|

The basis of food selection in flounders, Platichthys flesus (L.), in the Severn Estuary

Abstract: The factors influencing the selection of food by flounders, Platichthys Jlesus (L.), have been investigated by analysing collections made in the Severn Estuary for 1 year and the results of experiments. Flounders measuring between 6.0 and 35 cm fed heavily on the polychaete Nereis diversicolor in February and on the amphipod Gammarus salinus between February and April. Thereafter these species were replaced by the mysid Neomysis integer with the decapod Crangon iwlgaris. Hounders shorter than 6.0 cm, fed mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 19 publications
1
62
0
2
Order By: Relevance
“…Intuitively, turbidity should reduce the prey field of a predator by reducing light and visibility and thus the number of successful encounters. Narrowing of the prey field by turbidity has been reported for bluegill Lepomis macrochirus (Vinyard & O'Brien 1976) and flounder Platichthys flesus (Moore & Moore 1976). Swenson & Matson (1976) reported no reduction in feeding rate by larval lake herring Coregonus artedii at moderate turbidities (28 ppm), but they did note that larvae aggregated closer to the surface in turbid water.…”
Section: Growth and Foragingmentioning
confidence: 96%
“…Intuitively, turbidity should reduce the prey field of a predator by reducing light and visibility and thus the number of successful encounters. Narrowing of the prey field by turbidity has been reported for bluegill Lepomis macrochirus (Vinyard & O'Brien 1976) and flounder Platichthys flesus (Moore & Moore 1976). Swenson & Matson (1976) reported no reduction in feeding rate by larval lake herring Coregonus artedii at moderate turbidities (28 ppm), but they did note that larvae aggregated closer to the surface in turbid water.…”
Section: Growth and Foragingmentioning
confidence: 96%
“…Beyst et al, 1999;Cabral 2000b;Darnaude et al, 2001), which emphasizes a generalist and an opportunistic utilization of these food resources (Lasiak and McLachlan, 1987;Beyst et al, 1999). Furthermore, niche overlap is usually minimized by differences in resource use in other niche dimensions, namely time and space (Moore and Moore, 1976;Poxton et al, 1983;Burke, 1995). Darnaud et al (2001) studied the food portioning among juvenile flatfishes in a Mediterranean coastal shallow area and found that diet overlap was low.…”
Section: Discussionmentioning
confidence: 99%
“…Fish feed opportunistically yet are often selective in their diets [5][6][7]. The main factors that determine the type of prey are feeding preference [8][9][10], availability of prey, prey mobility and its distribution in the water column, catching efficiency of the predator, water temperature and turbidity [11]. Changes in feeding habits of a fish species are a function of the interactions among several environmental factors that influence the selection of food item [12].…”
Section: Introductionmentioning
confidence: 99%